Self-study problems/solutions book 2, chapters 13-27, to accompany Accounting principles, Jerry J. Weygandt, Donald E. Kieso, Walter G. Kell - Hunt, Marilyn F.; Weygandt, Jerry J. (Wiley, 1996)
The most complete guide available to help professionals sharpen their accounting and business skills. This unique reference features a logically structured framework that details accounting practices step-by-step, as well as all the newest innovations in the field.